Fragments : architecture of the Holocaust ; an artist's journey through the camps - Koenig, Karl P. 1938-2012 (Fresco Fine Art Publ, 2011)
A collection of 61 black-and-white full-page (some folded) photographs of the architecture from ten concentration camps: Mauthausen (Austria), Breendock (Belgium), Theresienstadt (Czech Republic), Buchenwald, Dachau, and Sachsenhausen (Germany), Vucht (The Netherlands), and Auschwitz I, Auschwitz II at Birkenau, and Majdanek (Poland)